2016
DOI: 10.1016/j.rse.2015.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Burned forest characterization at single-tree level with airborne laser scanning for assessing wildlife habitat

Abstract: Abundance, size, and spatial distribution of standing dead trees (snags), are key indicators of forest biodiversity and ecosystem health. These metrics represent critical habitat components for various wildlife species of conservation concern, including the Black-backed Woodpecker (Picoides arcticus), which is strongly associated with 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 67 publications
2
53
0
Order By: Relevance
“…However, urban environments often have a broad mix of tree species and trees of different heights and crown shapes, which makes the ITC analysis more challenging [76]. Another application is for habitat analysis, where detailed information about the trees can provide information that is not otherwise available for large areas about the height distribution or layering, tree species composition, and site condition [77] or standing dead trees and burnt forest [78].…”
Section: Habitat Analysis and Urban Mappingmentioning
confidence: 99%
“…However, urban environments often have a broad mix of tree species and trees of different heights and crown shapes, which makes the ITC analysis more challenging [76]. Another application is for habitat analysis, where detailed information about the trees can provide information that is not otherwise available for large areas about the height distribution or layering, tree species composition, and site condition [77] or standing dead trees and burnt forest [78].…”
Section: Habitat Analysis and Urban Mappingmentioning
confidence: 99%
“…The fire burned through a mosaic of vegetation types that vary with elevation, which included low-elevation grasslands, chaparral and foothill-oak woodland savanna habitat, mixed conifer-broadleaf forests dominated by pines in the lower montane zone, and mixed conifer forests in higher elevation areas dominated by firs. A more detailed description of the study site can be found in Casas et al [26]. …”
Section: Study Areamentioning
confidence: 99%
“…This finding corresponds to results documented by Lefsky et al [30], who found a strong relationship for ALS-based TD estimates considering a DBH > 100 cm (R 2 = 0.85). Casas et al [88] report a TD estimation accuracy of 87% for trees with a DBH > 30 cm. The dependency of the TD estimation accuracy on DBH indicates a sensitivity issue of the applied ALS-LM approach, while mainly small trees cannot be differentiated and reliably identified.…”
Section: Reliability Of Tree Density Retrievalmentioning
confidence: 99%